Incidence of External Ear Canal Folliculitis - Mohammad Iqbal, Kamran Iqbal,Sahibzada Fawad Khan,Wasim Ahmad (Journal of Rawalpindi Medical College, 2017)
To analyze the incidence of External Ear Canal Folliculitis (EECF) in adult population of district Bannu. Methods: In this descriptive study 100 patients with ear ache, presented in four quarters of the year were included. Complaints, and findings on physical examination including otoscopy results, diagnosis were recorded. Inclusion criteria was adults (18+) with ear pain as a major complaint. We included the cases with another major complaint only when it was related to the ear pain (e.g. referred pain from sinusitis, tonsillitis).Exclusion criteria was antibiotic treatment in the last 10 days was marked as exclusion criteria. Both the rates of external ear canal folliculitis and the rate of Non-external ear canal folliculitis were compared. We also subdivided the different diagnostics under the title "folliculitis channel of the non-outer ear." The prevalence of the external ear canal folliculitis diagnosis was calculated, including subdivisionby sex and age groups, by location in the ear canal including posterior vs. anterior and by the quarters of the year. Results: 35% of cases represented EECF were included. The ratio of male to female was observed 3: 2. The condition was maximum in 2nd& 3rd quarter of the year where as it was minimal in 1st and 4th quarters. Earache in adult patients was the most common principal inflammation, which is generally termed as EECF. Conclusion: Different factors are being involved in its prevalence including poor hygiene, over crowding, bath in a contaminated water, hot weather, ear wax and lack of specialized care. Since treatment is only possible upon clinical diagnosis, doctors will likely be more reserved about oral antibiotics if EECF can be diagnosed appropriately